The study of meat and meat by-products of carcase. I. Striated muscular tissue - ΠΑΠΑΔΟΠΟΥΛΟΣ ΧΡΥΣΑΝΘΟΣ TP. (Journal of the Hellenic Veterinary Medical Society, 2019)
Meat it defined as the flesh of animals med as food. In practice this definition is restricted to a few dozen of the 3000 mammalian species; but k is often widened to include, as w d as the musculature, organs such as Over and kidney, brains and other edible tissue. The buk of the meat consumed is derived from sheep, cattle and pigs. The essential structural unit of all muscles is the fibre. Fibres are long, narrow, multinucleated cells which may stretch from one end of the muscle to the other and may attain a length of 34 cm. although they are only 10-100 micron in diameter. In healthy animals tine diameters of muscle fibres differ from one muscle to another and between species, breeds and sexes. They are increased by age, plane of nutrition and training. In a broad sense the composition of meat can be approximated to 75 per cent of water, 18 per cent of protein, 3.5 per cent of soluble, non-protein, substances and 3 per cent of fat, but an understanding of the nature and behaviour of meat, and of ks variabffity, cannot be based on such a simplification.